New Silver(I) Coordination Compound Loaded into Polymeric Nanoparticles as a Strategy to Improve in Vitro Anti- Helicobacter pylori Activity - Almeida Furquim De Camargo, Bruna [UNESP]; Soares Silva, Débora Eduarda [UNESP]; Noronha Da Silva, Anderson [UNESP]; Campos, Débora Leite [UNESP]; MacHado Ribeiro, Tamara Renata [UNESP]; Mieli, Maria Júlia; Borges Teixeira Zanatta, Melina [UNESP]; Bento Da Silva, Patrícia [UNESP]; Pavan, Fernando Rogerio [UNESP]; Gallina Moreira, Cristiano [UNESP]; Resende, Flávia Aparecida; Menegário, Amauri Antônio [UNESP]; et al. (American Chemical Society (ACS), 2020)
Helicobacter pylori inhabits the gastric epithelium and can promote the development of gastric disorders, such as peptic ulcers, acute and chronic gastritis, mucosal lymphoid tissue (MALT), and gastric adenocarcinomas. To use nanotechnology as a tool to increase the antibacterial activity of silver I [Ag(I)] compounds, this study suggests a new strategy for H. pylori infections, which have hitherto been difficult to control. [Ag (PhTSC·HCl)2] (NO3)·H2O (compound 1) was synthesized, characterized, and loaded into polymeric nanoparticles (PN1). PN1 had been developed by nanoprecipitation with poly(ϵ-caprolactone) polymer and poloxamer 407 surfactant. System characterization assays showed that the PNs had adequate particle sizes and ζ-potentials. Transmission electron microscopy confirmed the formation of polymeric nanoparticles (PNs). Compound 1 had a minimum inhibitory concentration for H. pylori of 3.90 μg/mL, which was potentiated to 0.781 μg/mL after loading. The minimum bactericidal concentration of 7.81 μg/mL was potentiated 5-fold to 1.56 μg/mL in PN. Compound 1 loaded in PN1 displayed better activity for H. pylori biofilm formation and mature biofilm. PN1 reduced the toxicity of compound 1 to MRC-5 cells. Loading compound 1 into PN1 inhibited the mutagenicity of the free compound. In vivo, the system allowed survival of Galleria mellonella larvae at a concentration of 200 μg/mL. This is the first demonstration of the antibacterial activity of a silver complex enclosed in polymeric nanoparticles against H. pylori.
Keywords: biofilm; Helicobacter pylori; polymeric nanoparticle; silver